Analisis Pengaruh Persepsi Manfaat, Persepsi Kemudahan Penggunaan dan Persepsi Risiko Terhadap Keputusan Pembelian dengan Kepercayaan Sebagai Variabel Intervening (Studi Pada Konsumen Gofood di Kota Semarang) - Widhiaswara, Isnaeni Agustin; Soesanto, Harry (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2020)
This study aims to analyze the effect of perceived usefulness, perceived of ease of use, perceived risk , trust and purchasing decisions for GoFood in the city of Semarang. Respondents in this study are consumers who make food purchases through GoFood. Data collected through Google Form containing questionnaires filled out by 125 respondents. The analytical method used is Structural Equation Modeling (SEM) analysis carried out with the AMOS program. The results of hypothesis testing with SEM show that: 1. Perceived usefulness has a significant effect on trust, 2. Perceived of ease of use has a significant effect on trust, 3. Perceived risk has a significant effect on trust, 4. Trust has a significant effect on purchasing decisions, 5. Perceived usefulness has a significant effect on purchasing decisions, 6. Perceived of ease of use has a significant effect on purchasing desicion, 7. Perceived risk has a significant effect on purchasing decisions.